Interaction of nitrogen dioxide with free base phthalocyanine - Białek, Beata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Quantum chemical ab initio method was used to investigate interactions between NO2 and H2Pc. Four possible sites for NO2 adsorption were considered. Full geometry optimisation together with frequency calculation was performed for the isolated molecules and the NO2–H2Pc complexes with the use of 6-31g(d, p) and minimal basis sets, respectively. Two stable and two transition states were found. The H2Pc molecular structure was found to be largely affected under the influence of NO2. It was found that for a certain chemisorption site H2Pc molecule might disintegrate and its building blocks could react with NO2 forming other species.
Optica Applicata, Vol. 35, 2005, nr 3, s. 323-328
Keywords: optyka; phthalocyanine; gas sensors; ab initio calculations